The Influence of Investment Profitability and Investment Risk on Individual Investment Decisions - Bagas Firmansyah; Mohammad Fajar Saputra; Hanif Dwi Hastungkara; Maria Yovita R. Pandin (Publikasi Inspirasi Indonesia, 2023)
Investment is one way to gain profits and increase wealth, research on understanding investment risks to individual investments is very important to understand. Research on Understanding Investment Risk in Individual Investments aims to determine the extent to which individuals understand investment risk, as well as how investment risk influences individual investment decisions. The results obtained show that understanding investment risks has a very positive influence on individual investment decisions in order to get the desired results.